COGNITIVE MANAGEMENT: THEORETICAL ASPECT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article highlights the theoretical foundations of cognitive management: prerequisites, leading concepts and principles of cognitive management, cognitive technologies, fundamentals of knowledge management and features of cognitive educational management.